2018
DOI: 10.1002/2017jd028126
|View full text |Cite
|
Sign up to set email alerts
|

High Spectral Resolution Spectroscopy of Sprites: A Natural Probe of the Mesosphere

Abstract: We present the first high spectral resolution (0.24 nm) spectra of sprites. These spectra were recorded in Europe in the summers and falls of 2015 and 2016 and during January 2017. The use of high spectral resolution has allowed us to resolve for the first time the internal (vibrorotational) structure of the sprite molecular N2 first positive system and to quantify the local gas (rotational) temperature of the mesosphere under the influence of sprites revealing that there is no measurable heating of the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…To perform this long‐time simulation of a single halo, we have avoided the sprite inception problem simulating a second discharge that removes the electric field produced by the first one several milliseconds later. The calculated spectra agree with previous model results (Gordillo‐Vázquez et al, , ) and with the spectra of the FP system of N 2 of sprites detected by Kanmae et al () and more recently with the high‐resolution sprite spectra reported by Gordillo‐Vázquez et al (). In addition, our models predict a nonnegligible enhancement of local mesospheric N 2 O, NO, and metastable species as a consequence of this glow discharge.…”
Section: Discussionsupporting
confidence: 91%
“…To perform this long‐time simulation of a single halo, we have avoided the sprite inception problem simulating a second discharge that removes the electric field produced by the first one several milliseconds later. The calculated spectra agree with previous model results (Gordillo‐Vázquez et al, , ) and with the spectra of the FP system of N 2 of sprites detected by Kanmae et al () and more recently with the high‐resolution sprite spectra reported by Gordillo‐Vázquez et al (). In addition, our models predict a nonnegligible enhancement of local mesospheric N 2 O, NO, and metastable species as a consequence of this glow discharge.…”
Section: Discussionsupporting
confidence: 91%
“…The chemical impact and optical signatures of TLEs have been widely investigated by several authors (Gordillo‐Vázquez, ; Kuo et al, ; Parra‐Rojas, Luque, & Gordillo‐Vázquez, ; ; Sentman et al, ; Winkler & Notholt, ). There have also been some ground‐, balloon‐, plane‐, and space‐based instrumentation devoted to the study of TLEs, such as the Imager of Sprites and Upper Atmospheric Lightning (ISUAL; Chern et al, ; Hsu et al, ) of the National Space Organization, Taiwan, that was in operation between May 2004 and June 2016, the Global LIghtning and sprite MeasurementS (GLIMS; Adachi et al, ; Sato et al, ) of the Japan Aerospace Exploration Agency between 2012 and 2015, and the GRAnada Sprite Spectrograph and Polarimeter (Gordillo‐Vázquez et al, ; Parra‐Rojas, Passas, et al, ; Passas et al, , ) and the high‐speed ground‐based photometer array known as PIPER (Marshall et al, ), both of them currently in operation. Despite the valuable advance in the knowledge of TLEs in the last decades, there are still several open questions about the inception and evolution of these events or their global chemical influence in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure c, we also show the synthetic spectrum of T v 5000 K with green lines from the observation by Kanmae et al () and with magenta dots from the high spectral resolution 0.24 nm results of Gordillo‐Vázquez et al (). The observed spectra by Kanmae et al () and Gordillo‐Vázquez et al () are in better agreement with our simulated spectrum T v 5000 K than the results with T v 1000, 3000, and 7000 K. The high spectral resolution 0.24 nm results from a ground observation by Gordillo‐Vázquez et al () show the strong water vapor absorption at 762 nm (downward‐pointing triangle of Figure c), while our simulated spectrum T v 5000 K is used for space observation in which the 762 nm absorption is less important, also shown in Figure b.…”
Section: Interpretation Of Isual Multiband Emission Ratios From Tle Smentioning
confidence: 94%
“…The SPARTAN results are also compared with the spectrum calculation in the work of Kuo et al (2008) where T v = 1000, 3000, 5000, and 7000 K in Figures 2a-2d, Figure 2. The spectrum obtained from the simulation work of Kuo et al (2008) and SPARTAN with vibrational temperatures (a) 1000 K, (b) 3000 K, (c) 5000 K, and (d) 7000 K. In panel (c), we also compare the synthetic spectra with green lines from the observation by Kanmae et al (2007) and with magenta dots from the high spectral resolution (0.24 nm) results of Gordillo-Vázquez et al (2018). The downward-pointing triangle with magenta color shows the strong water vapor absorption at 762 nm for spectra observation .…”
Section: Interpretation Of Isual Multiband Emission Ratios From Tle Smentioning
confidence: 99%
See 1 more Smart Citation